A study on determinants of commercial bank profitability during post merger / Nur Fariha Mohd Sohaimi - Mohd Sohaimi, Nur Fariha (2011)
This paper examines what are the determinants of commercial banks profitability during post merger. Guided merger was implemented in 2002 by the central bank of Malaysia to reform 54 of depository institutions into 10 large banks. This study conducted to utilized the secondary data obtained primarily from the banks web sites for eight commercial banks i.e. . Affin Bank, CIMB Bank, EON Bank, Maybank, Hong Leong Bank, Public Bank, RHB Bank and Am Bank during the period 2002 to 2009 by using PANEL data analysis. The results show that the capital ratio most significant in contribute to the bank profitability. A well capitalised bank is perceived to be of lower risk and will contribute to the higher profitability. On the other hand, bank size also have a positive relationship with the profitability. Means that the size of the banks measure by the total assets of the banks. Perceive its indicate that larger bank is more competitive and efficient since banks with a large retail deposit-taking network do not necessarily gain a cost advantage. So it will increase the profitability of the banks.